Luxury Brand Management: Global Research Trend Mapping - Loso Judijanto (West Science Business and Management, 2025)
This study aims to systematically map the global research landscape of Luxury Brand Management by employing a bibliometric approach to identify its intellectual structure, dominant themes, collaborative patterns, and evolving research trends. Using bibliographic data retrieved from the Scopus database, the study applies co-authorship, affiliation, keyword co-occurrence, citation, density, network, and overlay analyses through VOSviewer. The findings reveal that luxury brand management research is strongly anchored in brand management, marketing, and consumer behavior, forming the core theoretical foundation of the field. Over time, the research focus has expanded from traditional, exclusivity-driven branding perspectives toward more relational, digital, and sustainability-oriented themes, including social media, fashion, innovation, and sustainable development. The results also highlight a fragmented yet interconnected global collaboration structure, with a limited number of influential authors and institutions acting as key knowledge hubs. By providing a comprehensive and data-driven overview, this study contributes to a clearer understanding of the field’s evolution, identifies research gaps, and offers valuable insights for both scholars and practitioners seeking to advance theory development and strategic decision-making in contemporary luxury brand management.